Ketahanan Keluarga Pedagang Kaki Lima dalam Pemenuhan Kebutuhan di Masa Pandemi; Studi Lapangan Pedagang Kaki Lima Di Sekitar Kampus UIN Sunan Kalijaga - Andri Amin Tawakal; Ahmad Budi Lakuanine; Farhan Zikry; Hamsah Hudafi; Ahmad Hasan Basri (Faculty of Sharia and Law UIN Syarif Hidayatullah Jakarta, 2021)
Abstract This article discusses the consequences of the Covid-19 pandemic. From health to economic factors, including the impact on street vendors in the vicinity of the UIN Sunan Kalijaga campus, The implementation of Work from Home (WFH), in which workers, lecturers, and students conduct lectures via online “Daring,” and schoolchildren learn from home, has had the greatest impact on street vendors on campus. The purpose of this research is to discover how street vendors maintain family resilience. This study is a descriptive analytical field study that provides an overview of family resilience for street vendors via interviews conducted on the UIN Sunan Kalijaga Yogyakarta campus. According to the study's findings, performing the role and function of maintaining household resilience is an obligation even during the Pandemic.Keywords: Family Resilience; Role; Family Function Abstrak:Tulisan ini menjelaskan tentang Dampak pandemi Covid-19. Mulai dari faktor kesehatan hingga ekonomi, termasuk dampaknya bagi para pedagang kaki lima di sekitar kampus UIN Sunan Kalijaga. Pengaruh paling besar yang dirasakan oleh para pedagang kaki lima di sekitaran kampus ialah pemberlakuan Work from Home (WFH), dimana para pekerja, dosen, dan mahasiswa melakukan kuliah melalui online “Daring”, serta anak-anak sekolah belajar dari rumah. Penelitian ini bertujuan mencari tahu cara para pedagang kaki lima dalam menjaga ketahanan keluarga. Penelitian ini merupakan studi lapangan yang bersifat deskriptif analitis dimana memberikan gambaran tentang ketahanan keluarga bagi pedagang kaki lima melalui hasil wawancara di sekitaran kampus UIN Sunan Kalijaga Yogyakarta. Hasil penelitian menyatakan bahwa menjalankan peran dan fungsi terjaganya ketahanan rumah tangga adalah kewajiban bahkan di masa Pandemi.Kata Kunci: Ketahanan Keluarga; Peran; Fungsi Keluarga